Evidence of Complexation between Plasticized Argentum Triflate and Chitosan by X-Ray Photoelectron Spectroscopy (XPS) - M.M, Ali A,; M.Z.A, Yahya; R, Puteh; F, Sonsudin; R, Yahya; M.A, Yarmo; A.K, Arof (Malaysian Journal of Science, 2002)
Chitosan with a molecular weight of 6 x 10Ã¢ÂÂµ g molÃ¢ÂÂ»Ã‚Â¹ was used in this study. Chitosan is doped with silver triflate (AgCFÃ¢â€šÆ’SOÃ¢â€šÆ’) to produce an ion-conducting polymer that can he used as an electrolyte in solid-state electrochemical cells. Ethylene carbonate (EC) was added to enhance electrical conductivity. The polymer film was prepared by the solution cast technique. X-ray diffraction (XRD) confirms the disruption of the crystalline order of plasticized chitosan upon complexation and their conversion to the amorphous state for samples that exhibit increasing electrical conductvity. Complexation is confirmed by x-ray photoelectron spectroscopy (XPS) whereby the signal peak ranging from 375.9 to 376.6 eV is attributable to Ag-N interaction.